Aspects of the geology, geochemistry and metamorphism of the lower orebody, Broken Hill deposit, Aggeneys - Hoffmann, Dennis (Department of Geological Sciences, 2016)
The Broken Hill deposit, Aggeneys, is a metamorphosed stratiform Cu-Pb-Zn-Ag sulphide deposit situated in the mid-Proterozoic supracrustal sequence of the Bushmanland Subprovince in the Namaqualand Metamorphic Complex. The deposit comprises two superposed orebodies, each consisting mainly of massive sulphide lenses and iron formation which are hosted within a metapelitic schist close to major quartzite horizons. This study is concerned with the tectonically lower orebody (LOB). The iron formation is magnetite-rich and contains varying proportions of (Fe,Mn)-rich silicates (garnet, amphibole, olivine, orthopyroxene, pyroxenoid), quartz and Cu-Pb-Zn-sulphides. These minerals occur in mm- to 5 cm-thick bands and are often traceable over tens of metres. The well preserved banding is considered to represent bedding. Five different varieties of silicate-rich mesobands in the iron formation can be distinguished based on the predominant mineral assemblage: (a) amphibole-olivine-quartz +/- garnet, (b) amphibole-quartz, (c) garnet-apatite-quartz +/- amphibole, (d) garnet-apatite-quartzorthopyroxene, (e) pyroxferroite-quartz +/- amphibole and (f) quartz. These rocks all contain magnetite, and Ba-rich biotite is common but is not always present.